2016
DOI: 10.3390/jcm5080073
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Exertional Desaturation Are Associated with Mortality in Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic lung disease that manifests in hypoxemia, inactivity, and poor prognosis. This study aimed to assess the prognostic role of physical activity (PA) and exertional desaturation (ED) with mortality in IPF. At baseline, 34 IPF patients (68 (50–81) years) were interviewed using the International Physical Activity Questionnaire (IPAQ), and SpO2 was assessed pre to post 6-min walking test (∆SpO2). Patients were prospectively followed up for 40 months. Receiver operatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 54 publications
2
32
0
1
Order By: Relevance
“…Recently, the ATS and ERS documented that inactivity among chronic respiratory disease patients is associated with poorer outcomes including higher mortality risk [6]. These reports were confirmed with findings in IPF patients on the association between low activity and poorer survival [9,11,25]. In addition, sitting and walking times, as we observed in the current study, were inversely correlated, providing preliminary evidence of their combined protective benefits against adverse events in IPF (Table 3, Fig.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Recently, the ATS and ERS documented that inactivity among chronic respiratory disease patients is associated with poorer outcomes including higher mortality risk [6]. These reports were confirmed with findings in IPF patients on the association between low activity and poorer survival [9,11,25]. In addition, sitting and walking times, as we observed in the current study, were inversely correlated, providing preliminary evidence of their combined protective benefits against adverse events in IPF (Table 3, Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, our group previously reported better survival in individuals with moderate and high compared to low physical activity levels among IPF patients [25]. While, Atkins et al [10] found only a trend towards an association between sedentary behaviors and mortality at 1 and 2 years' follow-up in IPF patients.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…An even more robust body of evidence shows that exercise tolerance represents a strong end-point to predict the prognosis of ILD patients [76]. In FELL et al's study [12], survival was retrospectively calculated from the date of the first CPET in 117 subjects with IPF.…”
Section: The Role Of Cardiopulmonary Exercise Test In Ildsmentioning
confidence: 99%
“…The diagnosis and management of the disease is complicated in the elderly population where the non-specific symptoms of cough and dyspnea can be attributed to other comorbidities like heart failure and chronic obstructive pulmonary disease. 21 Low mixed venous oxygen saturation has also been shown to be a poor predictor of survival in patients with pulmonary hypertension associated with chronic fibrosing idiopathic interstitial pneumonia. 19 Older age has been shown to worsen the prognosis of patients with IPF, supporting the results of this study.…”
Section: Discussionmentioning
confidence: 99%